2017
DOI: 10.1055/s-0037-1601593
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous insulin administration before nocturnal sleep decreases breakfast intake in healthy young and elderly subjects

Abstract: Peripheral insulin acts on the brain to regulate metabolic functions, in particular decreasing food intake and body weight. This concept has been supported by studies in humans relying on the intranasal route of administration, a method that permits the direct permeation of insulin into the CNS without substantial absorption into the blood stream. We investigated if intranasal insulin administration before nocturnal sleep, a period of reduced metabolic activity and largely absent external stimulation, affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Indeed, a number of publications reported absorption of small amounts of the nasally applied peptide hormone into the bloodstream . Our review of the literature showed that intranasal application of human insulin caused a decrease in blood glucose of between 0.2 mmol/L (4 mg/dL) and 0.5 mmol/L (9 mg/dL) in some studies . This decline in blood glucose persisted much longer than the temporary rise in circulating insulin after application of the insulin nasal spray.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, a number of publications reported absorption of small amounts of the nasally applied peptide hormone into the bloodstream . Our review of the literature showed that intranasal application of human insulin caused a decrease in blood glucose of between 0.2 mmol/L (4 mg/dL) and 0.5 mmol/L (9 mg/dL) in some studies . This decline in blood glucose persisted much longer than the temporary rise in circulating insulin after application of the insulin nasal spray.…”
Section: Discussionmentioning
confidence: 73%
“…45,50,57,61,63,67 Our review of the literature showed that intranasal application of human insulin caused a decrease in blood glucose of between 0.2 mmol/L (4 mg/dL) and 0.5 mmol/L (9 mg/dL) in some studies. 26,35,42,44,45,48,57,61,65,67 This decline in blood glucose persisted much longer than the temporary rise in circulating insulin after application of the insulin nasal spray. Hence, this is presumably not only attributable to the spillover of nasal insulin into the circulation, but also to enhanced peripheral insulin sensitivity caused by insulin action in the human brain.…”
Section: Discussionmentioning
confidence: 95%
“…47 In experiments investigating the impact of 160 IU of IN insulin administered before nocturnal sleep, both men and women ate less from a standardised breakfast buffet when they had received IN insulin compared to placebo. 65 This effect, which was found in young and elderly participants alike, implies that an acute enhancement of the central nervous insulin signal in the evening exerts a surprisingly durable attenuating effect on food intake across sleep as a period of relative metabolic inactivity. (For a summary of sex-specific effects of IN insulin, see Box 1; for a discussion of IN insulin effects on sleep-related parameters, see paragraph 4).…”
Section: Food Intake Body Weight and Energy Expenditurementioning
confidence: 97%
“…42 However, postprandial (but not preprandial) IN insulin administration decreased the intake of palatable snacks in women (men did not participate in the study), 44 and administering IN before nocturnal sleep curbed breakfast intake in men and women. 65 Neuroimaging experiments did not yield indicators of sexspecific IN insulin effects on food valuation. 63 Increasing circulating oestradiol at the same time as decreasing testosterone concentrations in healthy young men did not hamper the hypophagic effect of IN insulin.…”
Section: Box 1 Experimental Indicators Of Sex Differences In the Response To Intranasal Insulinmentioning
confidence: 99%
“…The intranasal insulin treatment has been shown in multiple human clinical trials to safely improve memory, attention, and functioning in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD), to improve memory, motor symptoms in patients with Parkinson (PD), to improve memory in adults with type 2 diabetes, and even to improve memory in normal healthy adults [57][58][59][60][61][62][63][64][65][66][67][68][69][70]. In addition, intranasal insulin has been studied with regard to food/eating behavior, diabetes (insulin resistance), stress axis, and sleep [71][72][73][74][75][76][77][78][79].…”
Section: Intranasal Insulinmentioning
confidence: 99%